Distribution of Factors Affecting Nursing Students’ Challenges in Student-Centered Learning - Ambo Anto; Faisal Faisal; Muhammad Fathur Rahman MT Hardjo; Rismanudin Rismanudin; Bertelomeus Hibu (Jurnal Ners, 2026)
Student-Centered Learning (SCL) has become an important instructional approach in nursing education because it encourages students to actively construct knowledge, strengthen critical thinking, and improve problem-solving abilities. Despite its educational benefits, nursing students frequently encounter various challenges that may limit the effectiveness of SCL implementation. These challenges are influenced by multiple factors, including individual characteristics, learning environments, institutional support, teaching strategies, and the availability of educational resources. This study aims to identify and describe the distribution of factors affecting nursing students’ challenges in Student-Centered Learning. A quantitative descriptive design was employed to examine the prevalence and distribution of these influencing factors among nursing students. Data were collected using a structured questionnaire and analyzed through descriptive statistical methods, including frequency and percentage distributions. The findings indicate that challenges experienced by nursing students are multidimensional, with the most prominent factors relating to learning readiness, time management, academic workload, lecturer facilitation, learning resources, and peer collaboration. The results suggest that successful implementation of Student-Centered Learning requires not only students’ active engagement but also adequate institutional support, effective instructional design, and a conducive learning environment. Understanding the distribution of these influencing factors provides valuable evidence for educators and higher education institutions to develop targeted strategies that enhance students’ learning experiences and improve the effectiveness of Student-Centered Learning in nursing education.